Biofabrication of novel silver and zinc oxide nanoparticles from Fusarium solani IOR 825 and their potential application in agriculture as biocontrol agents of phytopathogens, and seed germination and seedling growth promoters - Trzcińska-Wencel, Joanna; Wypij, Magdalena; Terzyk, Artur P.; Rai, Mahendra; Golińska, Patrycja (Frontiers in Chemistry, 2023)
Introduction: Plant pathogens adversely affect the growth and yield of crops, which leads to losses in food production. Metal-based nanoparticles (MNPs) can be a remedy to solve this problem. Methods: Novel silver nanoparticles (AgNPs) and zinc oxide nanoparticles (ZnONPs) were biosynthesized from Fusarium solani IOR825 and characterized using Dynamic Light Scattering, Fourier Transform Infrared spectroscopy, Transmission Electron Microscopy, Xray diffraction and measurement of Zeta potential. Antibacterial activity of NPs was evaluated against plant pathogenes by determination of the minimum inhibitory (MIC) and biocidal concentrations (MBC). Micro-broth dilution method and poisoned food technique were used to assess antifungal activity of NPs against plant pathogens. Effect of nanopriming with both types of MNPs on maize seed germination and seedlings growth was evaluated at a concentration range of 1-256 µgmL-1 . Results: Mycosynthesis of MNPs provided small (8.27nm), spherical and stable (zeta potential of -17.08mV) AgNPs with good crystallinity. Similarly, ZnONPs synthesized by using two different methods (ZnONPs(1) and ZnONPs(2)) were larger in size (117.79 and 175.12nm, respectively) with Zeta potential at -9.39 and -21.81mV, respectively. The FTIR spectra showed the functional groups of the capping molecules on the surface of MNPs. The MIC and MBC of AgNPs against bacteria ranged from 8 to 256 µgmL1 and from 512 to 1024µgmL-1, respectively. Both types of ZnONPs displayed antibacterial activity at 256-1024µgmL -1 (MIC) and 512-2048µgmL-1 (MBC), but in the concentration range tested, they revealed no activity against P.carotovorum. Moreover, AgNPs and ZnONPs inhibited the growth of A.lternata, F.culmorum, F.oxysporum, P.lingam, and S.sclerotiorum. MIC and MFC of AgNPs ranged from 16-128 and 16-2048µgmL-1. ZnONPs showed activity with MIC and MFC 128-2048 and 256-2048µgmL-1. The AgNPs at a concentration of ≥32µgmL-1 revealed sterilization effect on seeds while ZnONPs demonstrated stimulatory effect on seedlings growth at concentrations of ≥16µgmL-1 by improving the fresh and dry biomass production by 24 and 18-19%. Discussion: AgNPs and ZnONPs from F.solani IOR 825 could be applied in agriculture to prevent the spread of pathogens. In view of the potential of ZnONPs to stimulate plant, they could be crucial in increasing crop production from the perspective of current food assurance problems.